Optimization on dielectric properties of Y2Ti2O7 ceramics with Bi2O3-Nd2O3-Nb2O5 co-doping - 丁佳钰 王哲飞 龚志态 肖瑗 王丽熙 张其土 (Journal of rare earths, 2011)
The present work aimed to explore a kind of microwave dielectric materials with middle-permittivity, high Qf, near-zero τf, and lower sintering temperature. A series of Y2Ti2O7 microwave dielectric ceramics were synthesized by conventional solid-state method. For improving the dielectric properties of Y2Ti2O7 system, Bi2O3, Nd2O3 and Nb2O5 were added and their effects on phase composition, micro-structure, and dielectric properties at microwave frequencies were investigated by means of X-ray diffraction （XRD） and scanning electron microscopy （SEM）. The queuing score method for multi-target orthogonal design was used to obtain the optimum prescription. The results showed that the Y2Ti2O7 ceramics with 8 wt.% Bi2O3 and 1 mol.% Nd2O3-Nb2O5 were well sintered at 1350 ℃, exhibiting excellent dielectric characteristics, i.e. εr≈76, Qf≈18980 GHz, τf =＋25.5 ppm/℃.